2011
DOI: 10.1002/mus.21877
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of symptomatic diabetic patients with normal nerve conduction studies: Utility of cutaneous silent periods and autonomic tests

Abstract: Established electrophysiological methods have limited clinical utility in the diagnosis of small-fiber neuropathy (SFN). In this study, diabetic patients with clinically diagnosed SFN were evaluated with autonomic tests and cutaneous silent periods (CSPs). Thirty-one diabetic patients with clinically suspected SFN and normal nerve conduction studies were compared with 30 controls. In the upper extremities (UE), the CSP parameters did not differ statistically between the patient and control groups, whereas, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…Pinar et al (19) conducted a study to verify the parameters of the cutaneous silent period (latency and duration) in symptomatic diabetics, with clinically defined thin-fiber neuropathy and normal nerve conduction. The study included 31 diabetics and 30 healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Pinar et al (19) conducted a study to verify the parameters of the cutaneous silent period (latency and duration) in symptomatic diabetics, with clinically defined thin-fiber neuropathy and normal nerve conduction. The study included 31 diabetics and 30 healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Any defect in this inhibition process prolongs CSP latency by delaying motor neuron inhibition. Furthermore, during the inhibition of interneurons, more motor neurons are involved in the process as a result of any stimulation and, eventually, CSP duration shortens . It has been shown that technical and demographic factors and/or neuropathies may prolong CSP latency .…”
Section: Discussionmentioning
confidence: 99%
“…Его можно получить с помощью любого устройства для ЭМГ и использовать для изучения А-дельта-волокон при периферической нейропатии [45,46]. Это может быть полезным методом ранней диагностики диабетической нейропатии тонких волокон [43,47,48].…”
Section: диагностика ранней дпнunclassified
“…Симпатические кожные реакции используются для ранней диагностики автономной нейропатии [47]. В некоторых исследованиях были обнаружены следующие отклонения при ранних стадиях диабета и при нарушении толерантности к глюкозе: отсутствие симпатических кожных реакций, увеличение латентного периода и понижение амплитуды [49,50].…”
Section: диагностика ранней дпнunclassified